2004
DOI: 10.1111/j.1477-9552.2004.tb00095.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Relationship Between Aquaculture and Reduction Fisheries

Abstract: Recently, there has been a growing concern that increased aquaculture production poses an environmental threat to the species targeted in so‐called reduction fisheries, the main source for fishmeal. The argument is that increased aquaculture production leads to higher feed demand, and then presumably to higher fishing effort in these fisheries. In this paper we address whether aquaculture production threatens sustainability of such fisheries. First, we ask under which management regimes can increased demand po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 29 publications
1
47
0
1
Order By: Relevance
“…Based on monthly data of fishmeal and soybean prices between 1981 and 1999, it was found that fishmeal and soybean were strong rich protein meal substitutes [63] and that total supply and demand of these two protein meals were determinants of fishmeal prices. Given the vast environmental variability exacerbating the supply side for the anchovy industry, it is not surprising that mechanisms to cope with the demand side were evolved.…”
Section: Fourth Impact: Uncertain Changes In Fishmeal Pricesmentioning
confidence: 99%
“…Based on monthly data of fishmeal and soybean prices between 1981 and 1999, it was found that fishmeal and soybean were strong rich protein meal substitutes [63] and that total supply and demand of these two protein meals were determinants of fishmeal prices. Given the vast environmental variability exacerbating the supply side for the anchovy industry, it is not surprising that mechanisms to cope with the demand side were evolved.…”
Section: Fourth Impact: Uncertain Changes In Fishmeal Pricesmentioning
confidence: 99%
“…(Asche and Bjorndal, 1999;Asche and Tveterås, 2004). Soymeal, a close substitute for fishmeal in terms of crude protein, formerly prevented large changes in price for fishmeal despite the increase in demand (Asche and Tveterås, 2004;Asche et al, 2013). However, this price dynamic between fishmeal and soymeal has broken down in recent years (Asche et al, 2013) as fishmeal is substitutable only to a point in aquaculture diets.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other land-based farmers, feed will be substituted for other feeds if prices increase and quality is not compromised FIGURE 4 | Cross validation where half of the reported prices were removed to estimate the remaining half of the reported prices for DHC (direct human consumption) and FMFO/Other (fishmeal, fish oil and other uses) based on country, taxa, or at random. (Asche and Bjorndal, 1999;Asche and Tveterås, 2004). Soymeal, a close substitute for fishmeal in terms of crude protein, formerly prevented large changes in price for fishmeal despite the increase in demand (Asche and Tveterås, 2004;Asche et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, chickens require about two pounds of feed for every pound of meat that is produced. Other authors (Asche and Tveterås 2004) refute the existence of a 'fish meal trap' limiting growth since increased demand for feed cannot affect reasonably well-managed fish stocks in reduction fisheries, and even if stocks are mismanaged, fish feed demand will not have an effect as long as the fishmeal and oil markets are integrated with the similar but much larger vegetable meal and oil markets.…”
Section: Technological Improvements In Aquacultural Productionmentioning
confidence: 99%